Factors Influencing Employer Attitudes towards Vocational Education - Mccracken, J. David (1986)
This study tested a conceptual model to determine the strengths and directions of relationshzps between selected predictor variables and the attitude of employers about vocational education. Personal characteristics of employers and characteristics of the firm served as predictor variables. Variables significantly related with employer attitude were type of business, employee educational level, years in business, sex and age. The set of varaibles of personal characteristics and the firm each uniquely. explained a portion of the variance in employer attitudes. Whether or not the employer operated a service type of business and the sex of the employer were the two variables which best predicted employer attitude toward vocational education. Service employers and male employers possessed the more positive attitudes